Gambaran evaluasi fungsi ginjal (kadar ureum, kreatinin dan asam urat darah) pasca covid-19 di wilayah gang anwar tahun 2022 - Jannah, Insani Fitrahulil; Sari, Mike Permata; Radhina, Afifa (Indonesian Journal of Health Science, 2024)
Coronavirus Disease 2019 (COVID-19) is an acute respiratory syndrome caused by Coronavirus 2 (SARS-CoV-2), which is associated with several diseases, one of which is kidney disease due to the overactivation of the pro-inflammatory ACE/ANGII/AT1R pathway. This results in the overexpression of the ACE2 pathway, leading to an increased binding site for SARS-CoV-2, where the viral antigen can accumulate in the renal tubules and cause acute kidney injury. This research The aims to examine the evaluation of kidney function by measuring blood urea, creatinine, and uric acid levels after the PPKM process to observe any trends in the decline of kidney function among the respondents. Descriptive qualitative research method with a cross-sectional approach. The research subjects are 30 residents of Anwar Alley aged 40-70 years, using purposive sampling conducted in June-July 2022. The research results showed that the largest number of respondents were female, totaling 26 (86.7%), while male respondents numbered 4 (13.3%). The most common age category was 40-49 years, with 18 respondents. The average urea level is 19.19 mg/dl, creatinine is 1.03 mg/dl, and uric acid level is 6.13 mg/dl. There are 2 individuals with high urea levels, 6 individuals with high creatinine levels, and 14 individuals with high uric acid levels. The SARS-CoV-2 antigen can accumulate in the kidneys, potentially causing acute kidney injury, which is characterized by the presence of hematuria, proteinuria, and increased levels of blood urea and creatinine. Penyakit Coronavirus 2019 (COVID-19) adalah suatu sindrom pernafasan akut yang disebabkan oleh Coronavirus 2 (SARS-CoV-2) yang berasosiasi dengan beberapa penyakit salah satunya adalah penyakit ginjal karena adanya overaktivasi Pro immflamantory ACE/ANGII/AT1R yang mengakibatkan overekspresi jalur ACE2 yang menyebabkan peningkatan bindingsite dari SARS-CoV-2 dimana antigen virus bisa terakumulasi di tubulus ginjal dan menyebabkan cidera ginjal akut. Penelitian ini untuk melihat gambaran evaluasi fungsi ginjal dengan pengukuran nilai ureum, kreatinin dan asam urat darah setelah proses PPKM untuk melihat  adanya kecendurungan penurunan fungsi ginjal responden. Metode Penelitian kualitatif deskriptif dengan pendekatan Cross sectional. Subjek penelitian adalah 30 warga gang Anwar usia 40-70 tahun dengan teknik Purposive sampling ada bulan Juni-Juli 2022. Hasil Penelitian didapatkan jumlah responden terbnyak adalah perempuan sebesar 26(86.7%) dan laki-laki sebanyak 4(13,3%) dengan kategori usia terbanyak adalah usia 40-49 tahun sebanyak 18 responden. Rerata kadar ureum adalah 19,19  mg/dl, kreatinin sebesar 1,03  mg/dl dan kadar asam urat sebesar 6,13 mg/dl. Adapun jumlah kadar ureum responden yang tinggi terdapat 2 orang, kreatinin sebanyak 6 orang dan kadar asam urat yang tinggi  sebanyak 14 orang.  Antigen SARS-Cov-2 akan terakumulasi di ginjal yang bisa menyebakan cidera ginjal akut yang ditandai dengan adanya hematuria, proteinuria serta peningkatan nilai ureum dan kreatinin darah.